Stress Akademik pada Mahasiswa Rantau Tahun Pertama Kota Bandung - Nisrina Najwa; Umar Yusuf Supriatna (Bandung Conference Series: Psychology Science, 2024)
Abstract. Overseas students experience more stress than non-overseas students (Handayani, 2020). The stress felt by first-year overseas students comes from academic pressure. To deal with academic stress experienced by students, students need mental strength, namely patience. This study aims to determine how much impact patience has on academic stress and which aspects of patience have the most impact on academic stress in first-year overseas students in the city of Bandung. The research design used in this study is a quantitative study with a non-experimental causality design using a patience variable measuring tool compiled by Yusuf (2021) with a validity value range of 0.5-0.8 and a reliability of 0.93 and an academic stress measuring instrument constructed by Rizka Hadian Permana, S .Psi., M.Psi and Lilim Halimah, BHSc., MHSPY based on Sarafino's theory with a validity value range of 0.316-0.862 and a reliability of 0.977. The sampling technique used was inccidental sampling and 109 respondents were tested using multiple linear regression tests. The results of the multiple regression test show that there is a significant effect between patience and academic stress, with an r-square value of 0.400 or 40%. The aspects of patience that have a significant effect on academic stress are the aspects of steadfastness and perseverance. Abstrak. Mahasiswa rantau lebih banyak mengalami stres dibandingkan dengan mahasiswa yang bukan rantau (Handayani, 2020). Stres yang dirasakan mahasiswa rantau tahun pertama salah satunya bersumber dari tekanan akademik. Untuk menghadapi stres akademik yang dialami mahasiswa, maka mahasiswa memerlukan kekuatan mental yaitu kesabaran. Penelitian ini bertujuan untuk mengetahui seberapa besar pengaruh kesabaran terhadap stres akademik serta aspek kesabaran mana yang paling berpengaruh terhadap stres akademik pada mahasiswa rantau tahun pertama di Kota Bandung. Rancangan penelitian yang digunakan pada penelitian ini adalah penelitian kuantitatif dengan desain kausalitas non eksperimen menggunakan alat ukur variabel kesabaran yang disusun oleh Yusuf (2021) dengan rentang nilai validitas 0.5-0.8 dan reliabilitas 0.93 serta alat ukur stres akademik yang dikonstruksikan oleh Rizka Hadian Permana, S.Psi., M.Psi dan Lilim Halimah, BHSc., MHSPY berdasarkan teori Sarafino dengan rentang nilai validitas 0.316-0.862 dan reliabilitas 0.977. Teknik sampling yang digunakan adalah inccidental sampling dan mendapatkan 109 responden yang diuji dengan uji regresi linear berganda. Hasil uji regresi berganda menunjukkan bahwa ada pengaruh signifikan antara kesabaran dan stres akademik, dengan nilai r-square sebesar 0.400 atau 40%. Adapun aspek kesabaran yang berpengaruh signifikan terhadap stres akademik adalah aspek tabah dan tekun.